2016
DOI: 10.1002/2016gl070052
|View full text |Cite
|
Sign up to set email alerts
|

The effect of atmospheric sulfate reductions on diffuse radiation and photosynthesis in the United States during 1995–2013

Abstract: Aerosol optical depth (AOD) has been shown to influence the global carbon sink by increasing the fraction of diffuse light, which increases photosynthesis over a greater fraction of the vegetated canopy. Between 1995 and 2013, U.S. SO2 emissions declined by over 70%, coinciding with observed AOD reductions of 3.0 ± 0.6% yr−1 over the eastern U.S. In the Community Earth System Model (CESM), these trends cause diffuse light to decrease regionally by almost 0.6% yr−1, leading to declines in gross primary producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…For crop yield, the impact of nitrogen deposition we find is also consistent in sign with Liu et al (2013) over China. We underpredict the effect of nitrogen deposition on crops compared to the metric of sourced nitrogen content used by Ladha et al (2016). This may be due to our relatively short assumed nitrogen deposition time frame.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For crop yield, the impact of nitrogen deposition we find is also consistent in sign with Liu et al (2013) over China. We underpredict the effect of nitrogen deposition on crops compared to the metric of sourced nitrogen content used by Ladha et al (2016). This may be due to our relatively short assumed nitrogen deposition time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Lassaletta et al (2014) develop relationships between observed total nitrogen input and crop yield on a countrywide basis, but they do not disaggregate the impacts of deposition saying only that the input from deposition is small, but not negligible. While Ladha et al (2016) estimate that 6 % of nitrogen contained in global maize, wheat, and rice comes from deposited nitrogen, to date, there has been no global study of the change of yield associated with nitrogen deposition, with most studies concentrating on the impacts of nitrogen deposition on interactions with atmospheric CO 2 and carbon storage. Folberth et al (2016) neglect nitrogen deposition in their study of soil and meteorological data uncertainties in crop models due to the lack of available deposition data in a form suitable for global crop models.…”
Section: D Schiferl Et Al: Resource and Physiological Constraintmentioning
confidence: 99%
See 1 more Smart Citation
“…Across North America, emissions of nitrogen oxides (NO x ), sulphur dioxide (SO 2 ), and most other air pollutants (with ammonia being the exception) have declined in recent decades as a result of emissions regulations on cars and power plants, including, e.g., the use of flue gas de-sulfurization (FGD), and an overall reduction in the use of coal (e.g., Kharol et al 2017). As a result, there is a decreasing trend in aerosol that can be detected from satellite observations of aerosol optical depth (AOD) over south-eastern Canada (e.g., Boys et al 2014;Keppel-Aleks and Washenfelder 2016). These changes in aerosols have led to significant health-related improvements for Canadians (2000-2011) (Stieb et al 2015).…”
Section: Air Quality At Northern Latitudesmentioning
confidence: 99%
“…Different relative levels of these forms result in different irradiance patterns within plant canopies (Norman & Welles, ) and across heterogeneous terrain (Oliphant et al, , ) (see Table for a list of symbols). For example, global photosynthetically active radiation (PAR G )—a spectral subset of K G —is more efficient for canopy photosynthesis under conditions of diffuse beam PAR (PAR D ) than direct beam PAR (PAR S ) per unit PAR (Alton, ; Cheng et al, , ; Gu et al, , ; Keppel‐Aleks & Washenfelder, ; Mercado et al, ; Oliphant et al, ). Furthermore, the ratio of K D to K G has been found to lower the Bowen ratio (the ratio of sensible to latent heat flux) in a number of ecosystems (Steiner et al, ) and is important for the spatial distribution of net radiation in complex natural and urban terrain (e.g., Lindberg et al, ; Oliphant et al, ).…”
Section: Introductionmentioning
confidence: 99%